2001
DOI: 10.1159/000049292
|View full text |Cite
|
Sign up to set email alerts
|

Memory Deficits in Patients with DSM-IV Obsessive-Compulsive Disorder

Abstract: Neuropsychological testing provides increasing evidence that certain memory deficits might play an essential role in the emergence of doubts and, as a result, in perpetuating checkers’ rituals. Another account of doubting implicates metacognitive factors, such as confidence in memory. The present study examined mnestic functioning and self-perception of memory ability in a group of 27 nondepressed patients with obsessive-compulsive disorder (OCD) and 27 normal controls. All patients met DSM-IV and ICD-10 crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 12 publications
(16 reference statements)
5
62
0
4
Order By: Relevance
“…Concurrently, several studies reported memory impairments and response uncertainty as features often appearing in the OCD population (O'Connor et al, 2005). Poorer performance has been observed on tests of logical memory (Sher et al, 1984), short-term (Boone et al, 1991;Christensen et al, 1992) and long-term (Zitterl et al, 2001) visual memory in participants with OCD. It has also been proposed that uncertainty and low confidence level could impede information processing in patients with OCD and mediate their memory difficulties.…”
Section: Influence Of Obsessive-compulsive Symptoms On Erp Profilementioning
confidence: 97%
See 1 more Smart Citation
“…Concurrently, several studies reported memory impairments and response uncertainty as features often appearing in the OCD population (O'Connor et al, 2005). Poorer performance has been observed on tests of logical memory (Sher et al, 1984), short-term (Boone et al, 1991;Christensen et al, 1992) and long-term (Zitterl et al, 2001) visual memory in participants with OCD. It has also been proposed that uncertainty and low confidence level could impede information processing in patients with OCD and mediate their memory difficulties.…”
Section: Influence Of Obsessive-compulsive Symptoms On Erp Profilementioning
confidence: 97%
“…Repetitive thoughts and actions characterizing OCD could occur because of repeated neural signals indicating that they have not been adequately carried out (Pitman, 1987). The resulting uncertainty could impact on memory functions and, consequently, on the capacity to inhibit thoughts and actions (Zitterl et al, 2001). …”
Section: Influence Of Obsessive-compulsive Symptoms On Erp Profilementioning
confidence: 99%
“…Moritz and Woodward [61] found a positive relationship between symptoms of delusions and hallucinations and elevated levels of confidence in a word learning task; however, passivity experiences were not included either. Reduced levels of confidence in one’s own performance have been demonstrated for other psychiatric disorders like depression [62,63] and obsessive-compulsive disorder [64,65], leading to specific symptoms like rumination or checking, respectively. Regarding schizophrenia, more studies including patients with moderate-to-severe symptoms of ego disturbances are needed to investigate whether ego disturbances are associated with lower confidence in all performance tasks or only in source monitoring tasks, and whether patients with stronger symptoms, by contrast, show higher levels of confidence as suggested in the study by Moritz and Woodward [61].…”
Section: Discussionmentioning
confidence: 99%
“…B. die sog. "mnestic deficit hypothesis",d.h.dass der Zwang, v. a. der Kontrollzwang, auf eine Schwä-che mnestischer Leistung zurückzufüh-ren sei [28].Jedoch scheinen diese Ansät-ze wegen ihrer Orientierung nach der Kognition dem Willen kaum Beachtung zu schenken, während er von Jaspers [15] und Schneider [22] als ein wesentliches Moment des Zwangs angesehen wurde. Beiden Autoren zufolge ist der Zwang nur in dem Bereich des willkürlich geleiteten Seelenlebens möglich: "Die Grenze des möglichen Zwangs ist dort, wo die Grenze meines Willens ist" [15].…”
Section: Vor Dem Hintergrund Der Beachtlichenunclassified
“…Dafür spricht indirekt, dass Zwangssymptome bei Hirnorganikern "nur äußerst selten" vorkommen [2]. Diese klinische Tatsache erweckt in uns auch den Verdacht, ob der Kontrollzwang -wie die eingangs erwähnte Hypothese [10,28] annimmt -auf eine mnestische Störung zurückzuführen ist, weil sie eines der Kernsymptome der Hirnorganiker ist.…”
unclassified